ANALISIS SWOT PROGRAM PEMBINAAN PRESTASI SEKOLAH SEPAKBOLA DJARUM KUDUS TAHUN 2021 - Muhammad Zaki Ambari; Kriswantoro Kriswantoro (Universitas Negeri Semarang, 2023)
This research was motivated by the Djarum Kudus Soccer School, which produced outstanding players up to the National level and the National team. The focus of the problem is the management of the achievement development program at the Djarum Kudus Soccer School. The study aimed to determine the management function of the achievement coaching program at the Djarum Kudus Soccer School in 2021. The research method used is qualitative research with a descriptive approach. Data collection techniques include observation, interviews and documentation. The instruments used are interview and documentation instruments. The data analysis model used in this study is the analysis of Strengths, Weaknesses, Opportunities, Threats. The research results at the Djarum Kudus Soccer School showed Strengths: free registration, adequate and proper facilities, awards for outstanding athletes. Weakness: the quality of the coach is not entirely good. Opportunities: financial support from PT Djarum. Threats: no competition. This study concluded that the Djarum Kudus football school achievement development program in terms of the SWOT analysis went well, including sufficient funds, adequate and proper facilities, no training fees, awards for outstanding athletes, and club management. However, the weakness was in the quality of the coach. Suggestions for the Djarum Kudus football school need to hold a regeneration of licensed coaches and make a written training program.